2021
DOI: 10.1017/s0950268821000121
|View full text |Cite
|
Sign up to set email alerts
|

Influences of reopening businesses and social venues: COVID-19 incidence rate in East Texas county

Abstract: As the on-going severe acute respiratory syndrome coronavirus 2 pandemic, we aimed to understand whether economic reopening (EROP) significantly influenced coronavirus disease 2019 (COVID-19) incidence. COVID-19 data from Texas Health and Human Services between March and August 2020 were analysed. COVID-19 incidence rate (cases per 100 000 population) was compared to statewide for selected urban and rural counties. We used joinpoint regression analysis to identify changes in trends of COVID-19 incidence and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…All these weakened measures have led to an increase in social interaction between people and their close contacts. Studies conducted by Siqueira et al (2020) and Le et al (2021) have also confirmed the impact of easing measures on increasing the number of infected people, while Chaurasia and Singh (2020), Ajbar et al (2021), andSimetin et al (2021) found the opposite; the easing of measures did not significantly affect the change in the number of infected people. Previous research has shown that interpersonal distance, which is violated in this case, was very important for reducing the number of infected in the early phase of the COVID-19 pandemic (Andersen 2020).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…All these weakened measures have led to an increase in social interaction between people and their close contacts. Studies conducted by Siqueira et al (2020) and Le et al (2021) have also confirmed the impact of easing measures on increasing the number of infected people, while Chaurasia and Singh (2020), Ajbar et al (2021), andSimetin et al (2021) found the opposite; the easing of measures did not significantly affect the change in the number of infected people. Previous research has shown that interpersonal distance, which is violated in this case, was very important for reducing the number of infected in the early phase of the COVID-19 pandemic (Andersen 2020).…”
Section: Discussionmentioning
confidence: 89%
“…Authors further claim that there is no empirical evidence that loosening measures (economic reopening) caused an increase in confirmed cases. Another study conducted in East Texas county showed that after loosening measures and reopening, followed by another reopening, the number of infected increased (Le et al 2021). However, after that, the number of infected trended downwards, which the authors attribute to people wearing facemasks in business and social settings.…”
Section: Introductionmentioning
confidence: 99%
“…We believe our report is also novel in illustrating an example of how large outbreaks in the context of the easing of social restrictions may be addressed. The outbreaks described here primarily affected those likely to initially return to social venues following their reopening: young adults [ 27 ], who were likely at low personal risk from severe infection [ 21 , 22 ]. This population may have been less motivated, compared to a more vulnerable population, to change their behaviours to reduce transmission or infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Infection rates in the UK county where the outbreaks described, however, increased in late July 2021, particularly amongst adults aged under 30 years [ 25 ]. Although there are reports of COVID-19 outbreaks following the reopening of schools [ 26 ], and studies of area-level incidence during the reopening of businesses and social venues [ 27 ], we are not aware of any published reports of outbreaks occurring directly after widespread reopening of businesses or social venues.…”
Section: Introductionmentioning
confidence: 99%